How AI and other microscopy advances answer complex life science questions - Lucas, Luciano (Laser focus world, 2023)
Lucas discusses how can artificial intelligence (AI) and other microscopy advances answer complex life science questions. Microscopy enabled by AI will improve life sciences research and development across key therapeutic categories. Promising developments include autonomous microscopy and multiplexed imaging coupled with Al-based algorithms for cell mapping. Multiplexed imaging can help oncology researchers characterize the tumor microenvironment, which can unlock new insights into cell-cell interactions and the behavior of immune cells. A 2021 study presented at the Society for Immunotherapy of Cancer annual meeting demonstrated the power of this approach in analyzing pancreatic ductal adenocarcinoma.